URGENCY POSITION USHUL FIQH IN DEVELOPMENT SHARIA ECONOMICS - Syafruddin Syam; Rizki Muhammad Haris; Syahrini Harahap (Universitas Islam Negeri Ar-Raniry, 2023)
The development of the sharia economy is currently an important spotlight because it is continuously progressing very rapidly both at the National and International level. The development of the sharia economy in question includes sharia based financial institutions such as sharia banking, baitul maal wat tamwil, sharia insurance, sharia pawnshops and others. Because the products available at Islamic financial institutions are different from non Islamic financial institutions, what can be a differentiating tool in in terms of determining the type of product is from the ushul fiqh framework in Islamic economic methodology. In writing this article, here the autther uses the library research method in order to determine the position of ushul fiqh in the field of Islamic economics